KORELASI ANTARA MOTIVASI DENGAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN KELAS IV SDN SEKECAMATAN TEBAS - Saputra, Rian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aimed to analyze the correlation between motivation and learning outcomes Citizenship Education Public Elementary School fourth grade districts Tebas. This research uses descriptive method with a form of research that studies relationships. The population in this study is the fourth grade students who are 65 learners. Samples in this study is the fourth grade students of SDN 01 Tebas, Tebas SDN 05 and SDN 16 Bekut. Research instrument used was a questionnaire motivation to learn as much as 15 questions. Data collection techniques in this study is the indirect communication techniques and techniques of documentary studies. The results show the motivation of learners in public elementary school districts is in excellent Tebas is 96%. While the study of students in the subject of Social Sciences gained value - average 69.06 is quite as it went on the value range 60 to 69. There is a relationship being between motivation and learning outcomes of students. This value is then compared with r table at 5% level for the db N = 65 is 0,244. Thus r count> r table 0.84 of> 0,244. In this study alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected because the value of r count larger than r table, which means that there is a correlation / relationship between the motivation of learners with learning outcomes of students learning Citizenship Education class IV public elementary school districts Tebas.   Keywords :.Motivation, Citizenship Education, and Learning Outcomes